Mediastinal ectopic thyroid tissue as diferential diagnostic problem: A case report - Stojanoski, Stefan; Bijelović, Milorad; Ilinčić, Branislava; Vučković, Dejan; Kozić, Duško; Medić Stojanoska, Milica (Vojnosanitetski pregled, 2022)
Introduction. Mediastinal ectopic thyroid tissue (ETT) represents a rare entity. Clinically, it can manifest with thyroid gland dysfunction or with symptoms and signs caused by a compressive effect on the surrounding structures, but in most cases it is an asymptomatic condition and incidental finding. All pathologic processes, including malignancy that can occur in the orthotopic thyroid gland can also develop in the ETT. Case report. We presented a case of a 17-year-old female with incidentally found mediastinal ETT. Besides ETT, the patient had an orthotopic thyroid gland and was euthyroid. During follow-up, mild compressive symptoms developed. Magnetic resonance imaging examination showed a non-significant increase of the mediastinal mass volume, but due to its morphological changes, a suspicion of another etiology was raised. A discrepancy between the positive technetium-99m pertechnetate and negative 131 iodine radionuclide imaging of the mediastinal mass was highly suspicious for malignancy. Surgery was performed and the pathologist confirmed that it was a colloid goiter in the mediastinal ETT. Conclusion. Mediastinal ectopic thyroid tissue should be taken into account in the differential diagnosis of the mediastinal tumor mass. An increase in the size of the mediastinal ETT, development of compressive symptoms or suspected malignant alteration require surgical treatment.
Keywords: congenital abnormalities; diagnosis, differential; histological techniques; mediastinal neoplasms; thyroid gland